1962
DOI: 10.1099/00221287-29-2-311
|View full text |Cite
|
Sign up to set email alerts
|

Some Metabolic Differences Between Thiobacillus thioparus, T. denitrificans and T. thiocyanoxidans

Abstract: SUMMARY Differences in behaviour of Thiobmillus thioparus, T. d.enitrijicans andT. thiocyanoxidans were found in growth experiments carried out in thiosulphate or thiocyanate containing media and using aerobic or anaerobic conditions. These differences were: T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1969
1969
1983
1983

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, low homology between these organisms indicate that they are distantly related to each other. "T. denitrificans" was differentiated from T. thioparus in the ability to denitrify in the presence of nitrate and the loss of the ability to grow anaerobically after serial aerobic subculture (24). Therefore, these organisms were considered to be separate species.…”
Section: Resultsmentioning
confidence: 99%
“…However, low homology between these organisms indicate that they are distantly related to each other. "T. denitrificans" was differentiated from T. thioparus in the ability to denitrify in the presence of nitrate and the loss of the ability to grow anaerobically after serial aerobic subculture (24). Therefore, these organisms were considered to be separate species.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrate could be used as an electron acceptor by cells containing polyglucose, yielding nitrite; COa was the only product formed from polyglucose by these cells (Beudeker, de Boer & Kuenen, in preparation). Interestingly, some years ago it was observed that T. thioparus continued to produce nitrite from nitrate under anaerobic conditions even when the electron donor, thiocyanate, was not further oxidized (Woolley et al 1962). This implies that an alterna tive electron donor, which might be polyglucose, was oxidized during this period.…”
Section: [ 46 ]mentioning
confidence: 99%
“…Tetrathionate accumulation has been reported for Thiobacillus thioparus (London & Rittenberg, 1964), T. neapolitanus (Parker & Prisk, I 953), T. thiooxidans (Okuzumi & Kita, 1969, T. denitrzjicans (Woolley, Jones & Happold, 1962) and T. novellus (Vishniac & Trudinger,I 962). Conditions necessary for polythionate accumulation vary widely.…”
Section: Introductionmentioning
confidence: 99%